Virtual Learning Using Metaverse-Based Platform - Shan Shan; Zouy Wang (International Journal of Educational Technology and Artificial Intelligence, 2022)
Metaverse is the next iteration of the internet with a network of decentralized virtual spaces where users can socialize, learn and play. In addition, people leverage other new technologies (5G, blockchain, artificial intelligence), moving from 2D graphics on flat screens to 3D graphics on HMD. Metaverse will enable the creation of interactive and virtual equivalents of the physical world that we can explore via the extended reality platform. In educational institutions, the development of teaching materials is considered one of the main aspects that will encourage student learning and help achieve academic goals and objectives. In addition, educators need to innovate education under student characteristics and technological developments. This paper aims a guide for those who want to improve themselves in developing metaverse-based teaching materials for various fields of study. Learning in multiple subjects using metaverse-based learning materials is not dull for students. By mastering this material, it is hoped that you will be able to complete work related to the development of metaverse-based teaching materials.